Visible light mediated eosin-Y catalysed direct synthesis of biologically potent [1,2,4]Triazolo [3,4-b] [1,3,4] Thiadiazols (Indian Journal of Chemistry (IJC), 2024)
A green light promoted, facile, one-pot approach for the synthesis of biologically important 6-(substituted/unsubstituted benzylthio)-3-phenyl-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazole 6a-m has been developed. New synthetic approach for the preparation of tailor-made synthesis of triazolo [3,4-b] [1,3,4] thiadiazol derivatives 6a-m are in extremely high demand as they display significant potent activity against fungal strains as well as on mutant strains. Herein, we have designed an efficient, cheap and easy photo-induced synthetic strategy to obtain the target compound with excellent yield. Compounds 6a−m were evaluated in-vitro for their fungitoxicities against Penicillium citrinum and Fusarium oxysporum. All the synthesized compounds were found to be antifungal active. Among them, activities of some of the compounds displayed were comparable with that of the commercial fungicide griseofulvin and Dithane M-45. Structure activity relationships (SAR) for the screened compounds were discussed.